Bridging the gap: bioinspired robotics as catalyst for interdisciplinary education - Cayetano-Jiménez, Israel Ulises; Bustamante-Bello, Rogelio; Ramírez-Cadena, Miguel (Frontiers in Education, 2024)
Introduction In contemporary educational philosophy, constructivist and constructionist theories emphasize active knowledge construction among learners. These paradigms advocate for learners as active participants, engaging in knowledge creation through interaction and experience. Problem-Based Learning (PBL) exemplifies these principles by placing students at the center of hands-on challenges that foster critical thinking and collaborative problem-solving. This study explores the integration of these educational theories through an innovative pedagogical framework, focusing on the development of bioinspired robotics. Methods In a six-stage educational process at Tecnológico de Monterrey, 24 undergraduates were immersed in bioinspired robotics through workshops on animal biomechanics, soft robotics, and neuroscience. Organized into four teams, students designed robots for wildlife observation and search and rescue. The curriculum integrated theoretical lectures, hands-on training, and practical applications, emphasizing interdisciplinary collaboration and real-world problem-solving. This approach blended traditional education with innovative, project-based learning tailored to local and ecological challenges. Results The culmination of this initiative was marked by the creation of functional robotic prototypes, underscoring the effectiveness of the interdisciplinary approach. Post-project evaluations revealed marked enhancements in students' proficiency in both sciences and engineering. Furthermore, there was a pronounced strengthening of students' conviction regarding the importance of integrating bioinspired principles into engineering education. Discussion The study advocates merging traditional knowledge with modern technological innovation and bioinspiration to enhance learning outcomes. This integrated approach boosts analytical reasoning and scientific skills while also fostering empathy and emotional literacy, preparing students as holistic thinkers and versatile innovators. Combining biology, robotics, and education offers significant benefits, providing insights for educators and policymakers to equip students for future challenges. There is a strong consensus on the value of incorporating biological principles into engineering education, signaling a shift toward innovative, interdisciplinary curricula that enhance technical and broader cognitive skills.